PENGEMBANGAN BUKU AJAR PENDIDIKAN AGAMA ISLAM BERBASIS PENDIDIKAN KARAKTER DAN JIWA NASIONALIS - Isgandi, Yiyin; Prasodjo, Pandu (Universitas Pendidikan Indonesia, 2018)
The quality of Islamic Religion Education textbooks is still considered to be minimum. It has not been effective yet and been less valuable for pre-teacher students in teacher training and education university. This research aims to develop the PAI textbook based on characters education and nationalist soul in order to reduce radicalization towards religious understanding. Research method used in this research was research and development. The subjects and objects of this paper were PAI textbook and students of STKIP Al-Hikmah Surabaya. The data collected were analyzed both qualitatively and quantitatively. The results show that the book meets the needs of pre-teacher students. The students’ responses towards the effectiveness, the quality, the standardization, and the value of developed PAI Textbook products is higher than the old book. The newest handbook average percentage is 85% compared to the old book, which shows 50% in percentage. This book is very valid and worth to use. The results of joint validation according to the expert reviewers and the students indicate that this book is suitable to use and it is categorized as